Effects of fermented jujube powder on growth performance, rumen fermentation, and antioxidant properties of simmental bulls - Liu, Yongqing; Wang, Gaifang; Wang, Rui; Zhang, Xia; Feng, Caiping; He, Ying; Chu, Panpan (Frontiers in Veterinary Science, 2024)
Introduction: Fermented jujube powder (FJP) promotes a balance between the intestinal microflora and immune factors in animals. In this study, we aimed to investigate the effects of FJP on the production performance, nutrient digestion, rumen fermentation, and antioxidant properties of bulls. Methods: Forty Simmental bulls were randomly divided into four groups based on body weight and fed a basal diet with (5%, 7.5%, or 10% dry matter [DM]) or without FJP. The experimental period was 20 d for adaptation and 60 d for the feeding trial. Results: Dietary FJP supplementation did not affect DM intake (P > 0.05) but increased the average daily gain quadratically (P = 0.049) and decreased the feed conversion ratio linearly (P = 0.042). FJP quadratically enhanced DM and crude protein digestibility (P = 0.026 and P = 0.041, respectively) and linearly enhanced acid detergent fiber digestibility (P = 0.048). It also increased the total volatile fatty acid concentration quadratically (P = 0.037), acetate molar percentage, and acetate-to propionate ratio linearly (P = 0.002 and 0.001), and reduced the ammonia nitrogen concentration linearly (P = 0.003). Additionally, xylanase and protease activities and Ruminococcus flavefaciens abundance increased linearly (P = 0.006, 0.018, and 0.009, respectively), and total bacteria, Ruminococcus albus, and Ruminobacter amylophilus abundance increased quadratically (P = 0.047, 0.011, and 0.021, respectively). FJP linearly increased serum total protein concentration and antioxidant capacity (P = 0.003 and 0.018, respectively) and decreased malonaldehyde content (P = 0.006). Discussion: FJP supplementation (7.5%) enhanced production performance, nutrient digestion, rumen fermentation, and serum antioxidant capacity in bulls. The improved nutrient digestion may be due to an increase in ruminal microorganisms and total volatile fatty acids from the FJP. High blood antioxidant levels indicate that FJP may preserve proteins, thereby boosting the production performance of bulls.